Literasi Keuangan dan Finansial Teknologi Dalam Inklusi Keuangan Pada UMKM - Shifa, Layinnatus; Zahra , Meisyabela Ega; Novitasari , Fadilla; Yulianti , Eka; Saputri , Pungky Lela (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to analyze the influence of financial literacy and financial technology on financial inclusion in MSMEs in Genuk District, Semarang Regency. The main problem discussed was how understanding and using financial literacy and utilizing financial technology can support the sustainability and development of micro, small and medium enterprises (MSMEs). This research uses a qualitative approach using a descriptive method, where data is collected through in-depth interviews with four informants who are MSME owners in Genuk District, with different types of businesses, including food stalls, grocery stores, convection and laundry services. The results showed that the majority of informants had understood the basics of financial management, such as cash flow recording and the separation of personal and business finances. Additionally, the use of financial technologies such as digital wallets and P2P lending has helped informants improve transaction efficiency and expand their markets. Despite this, there are still obstacles in terms of accessibility of formal financial services, which some MSMEs find complicated, as well as a lack of in-depth understanding of the use of financial technology. This discussion emphasizes the importance of financial literacy and FinTech in supporting financial inclusion, but also identifies challenges that need to be overcome to encourage wider utilization of financial services. The conclusion of this research is that increasing financial literacy and utilizing financial technology can help MSMEs grow more efficiently and inclusively, although efforts are still needed to simplify procedures and improve financial education.